2010
DOI: 10.1227/01.neu.0000360374.59435.60
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of Perihematomal Edema and Sterile Meningitis With Intraventricular Administration of Tissue Plasminogen Activator in Patients With Intracerebral Hemorrhage

Abstract: Although IT-tPA hastens the resolution of IVH, it may worsen perihematomal edema formation. Larger prospective studies are required to confirm these findings and to determine whether outcome is adversely affected by IT-tPA administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
1
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 31 publications
2
27
1
1
Order By: Relevance
“…When comparing those results with the present study, several important differences should be considered. First, the mean ICH volume in the treatment and control group of Ducruet et al 14 was larger compared with our cohort. Moreover, there was an imbalance in the ICH size between the 2 groups, although the difference was not significant.…”
Section: Discussioncontrasting
confidence: 58%
See 4 more Smart Citations
“…When comparing those results with the present study, several important differences should be considered. First, the mean ICH volume in the treatment and control group of Ducruet et al 14 was larger compared with our cohort. Moreover, there was an imbalance in the ICH size between the 2 groups, although the difference was not significant.…”
Section: Discussioncontrasting
confidence: 58%
“…6,22 Furthermore, Ducruet et al 14 also reported increased occurrence of aseptic meningitis in rtPA-treated patients. 14 In our study, only the occurrence of ventriculitis without any further differentiation was recorded, and no significant difference was found between patients treated with IVF and controls.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations